2019
DOI: 10.1161/cir.0000000000000727
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Supervised Exercise Therapy for Patients With Symptomatic Peripheral Artery Disease: A Science Advisory From the American Heart Association

Abstract: Patients with lower-extremity peripheral artery disease (PAD) have greater functional impairment, faster functional decline, increased rates of mobility loss, and poorer quality of life than people without PAD. Supervised exercise therapy (SET) improves walking ability, overall functional status, and health-related quality of life in patients with symptomatic PAD. In 2017, the Centers for Medicare & Medicaid Services released a National Coverage Determination (CAG-00449N) for SET programs for patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 45 publications
0
109
1
2
Order By: Relevance
“…Exercise is also beneficial for other manifestation of atherosclerotic disease, such as coronaropathy or cerebrovascular disease, as well as for many other health conditions [ 38 , 39 , 40 ], and should therefore be encouraged in all patients with PAD. Guidelines from the European Society for Vascular Medicine and the American Heart Association recommend SET whenever available with a class of recommendation of either I B and I A, respectively [ 2 , 6 , 19 , 41 , 42 ]. The main obstacle for implementing SET as routine first line management is the lack of regional availability and patient’s motivation [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise is also beneficial for other manifestation of atherosclerotic disease, such as coronaropathy or cerebrovascular disease, as well as for many other health conditions [ 38 , 39 , 40 ], and should therefore be encouraged in all patients with PAD. Guidelines from the European Society for Vascular Medicine and the American Heart Association recommend SET whenever available with a class of recommendation of either I B and I A, respectively [ 2 , 6 , 19 , 41 , 42 ]. The main obstacle for implementing SET as routine first line management is the lack of regional availability and patient’s motivation [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other two thirds of the exercise training time were performed outdoors (if the weather allowed) with Nordic walking. The patients were taught the proper way of walking with the poles and were asked to walk until reaching a level of moderate-to-severe claudication, and then paused until complete resolution of the pain, before resuming walking [ 19 ]. During Nordic walking sessions, training intensity was mainly set at 12–14 on the 6–20 Borg scale (moderate intensity).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial treatment strategy is modification of cardiovascular risk factors, including smoking cessation, blood pressure and lipid control, optimizing blood sugar control, and exercise. 6 For symptomatic PAD, societal guidelines recommend a trial of medical treatment and supervised exercise therapy (SET) as first-line therapy, 7,8 with revascularization reserved for residual symptoms. 9 The Claudication: Exercise Versus Endoluminal Revascularization (CLEVER) study, which enrolled patients with claudication, found that SET with optimal medical therapy provided comparable durable improvement in functional status and HRQoL as compared with a combination of optimal medical therapy and revascularization.…”
Section: Current Treatment Options For Padmentioning
confidence: 99%
“…3,5 Several different studies have compared the effects of physical training on the 6MWTD and PFWD, whether aerobic exercises, strength training, or a combination of the two, and with durations ranging from 8 to 16 weeks. [6][7][8][9][10] However, after the intervention period, patients tend to give up on physical training.…”
Section: Introductionmentioning
confidence: 99%